Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Lin, Junyu; Xu, Dong; Li, Yue; Ye, Liming; Ge, Qian; Bian, Yeping; Han, Xibin; Zhang, Weiyan; Cheng, Shenghui (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex (E. rex) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.